Combatting Planktonic and Biofilm Populations of Carbapenem-Resistant Acinetobacter baumannii with Polymyxin-Based Combinations - Marisol Wences; Elliot R. Wolf; Cindy Li; Nidhi Singh; Nene Bah; Xing Tan; Yanqin Huang; Zackery P. Bulman (MDPI AG, 2022)
Carbapenem-resistant Acinetobacter baumannii (CRAB) can cause serious infections that are associated with high mortality rates. During the course of an infection, many CRAB isolates are able to form biofilms, which are recalcitrant to several antibiotics and can be difficult to treat. Polymyxin-based regimens are a first-line treatment option for CRAB infections, but they have not been optimized against both planktonic and biofilm phases of growth. The objective of this study was to identify polymyxin-based combinations that are active against planktonic and biofilm populations of CRAB. Four CRAB isolates (meropenem MICs: 8-256 mg/L) capable of forming biofilms were used in each experiment. The activities of polymyxin B alone and in combination with ampicillin/sulbactam, meropenem, minocycline, and rifampin were assessed using time-kill assays, with the CRAB isolates grown in planktonic and biofilm phases. Viable colony counts were used to detect the bactericidal activity and synergy of the antibiotic combinations. Against the planktonic populations, polymyxin B combined with meropenem, minocycline, ampicillin/sulbactam, and rifampin caused 3.78, −0.15, 4.38, and 3.23 mean log10 CFU/mL reductions against all isolates at 24 h, respectively. Polymyxin B combined with meropenem, ampicillin/sulbactam, or rifampin was synergistic against 75-100% (3/4 or 4/4) of CRAB isolates. Against biofilms, polymyxin B combined with meropenem, minocycline, ampicillin/sulbactam, and rifampin caused 1.86, 1.01, 0.66, and 3.55 mean log10 CFU/mL reductions against all isolates at 24 h, respectively. Only the combination of polymyxin B and rifampin retained bactericidal activity or synergy against any of the isolates when grown as biofilms (50% of isolates). The combination of polymyxin B and rifampin may be promising for CRAB infections that have planktonic and biofilm populations present.